STUDENTS’ VOICE: EFL SPEAKING PROBLEMS ON ENGLISH DAY PROGRAM AT ONE SENIOR HIGH SCHOOL IN INDONESIA - Noprival Noprival (Universitas Batanghari Jambi, 2016)
The purpose of this qualitative study was to examine the problems of speaking English encountered by students on English day at one senior high school in Jambi, Indonesia. The data were collected through demographic profiles and semi-structure in-depth interviews with senior high school students. The demographic data were analyzed descriptively while the interview data were transcribed and analyzed line by line to generate and develop codes and themes. Five salient themes that emerged in this research were (1) inadequate vocabulary knowledge, (1) grammar as a stumbling block, (3) fear of negative response from others, (4) low self-esteem to speak in English, and (5) feeling anxious to speak in English. Suggestions and implications are also discussed. Key words: English day, speaking problems, Indonesian students